Koncepcje społeczno-polityczne i gospodarcze Związku Naprawy Rzeczypospolitej (1926-1928) - Waingertner, Przemysław (Acta Universitatis Lodziensis. Folia Historica, 1997)
Związek Naprawy Rzeczypospolitej - ZNR, „Naprawa” (The League for Reforms of the Republic) came into existence on the turn of May and June 1926. It was organized by activists of secret Związek Patriotyczny (The Patriotic League) as a public representation of Związek Młodzieży Polskiej „Zet” (The League of Polish Youth „Zet”). „Naprawa” supported J. Pitsudski’s coup d’etat. It tried to create a political movement, supporting Piłsudski’s activity and creating an ideology for the sanacja political camp which was formed then. ZNR activists declared for democratic system and opposed dictatorship, however, they criticized parliamentary system, demanding presidential one. They supported a development of the municipal autonomy and tolerant policy towards national minorities, promoting state assimilation. ZNR supported also the etatism and state interventionism in economy. An important part played activists of the syndicalist wing of the league, who tried to create strong and independent from political parties trade unions, which should have an influence on the legislation and should become a support for the government. In the matter of foreign policy, „Naprawa” provided that Poland should stabilize political situation of Central-Eastern Europe. An analysis on the ZNR programm shows that it combined both rightist and leftist ideas. It is difficult to deline an ideological aspect of this organization. An attitude towards the state is an element which should make it possible to explain clearly the programm of „Naprawa”. The state was perceived by ZNR activists as the highest form of organization for political, economic, social and national life, as well as their political activity had reference to state interest.